ISOLATION AND IDENTIFICATION OF STREPTOCOCCUS SPP. IN PIGS WITH PORCINE RESPIRATORY DISEASE COMPLEX - Swandewi, Ni Kadek Meita; Besung, I Nengah Kerta; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana, 2021)
Streptococcus sp. is one of the primary causes of the Porcine Respiratory Disease Complex (PRDC). This research was conducted to study the bacteria Streptococcus sp. in the pig's respiratory tract sufferers Porcine Respiratory Disease Complex (PRDC) and distribution of the bacteria Streptococcus sp. in pre-weaned and post-weaned pigs. A total of 43 samples were nasal swab taken from pigs that showed PRDC symptoms such as depression, anorexia, dyspnea, the presence of exudates from the nasal, coughing / sneezing, and swelling of the joints. Samples were received from pig farms in Tabanan regency, Badung regency, and Gianyar regency. All samples were planted on sheep media so that blood was continued with the Gram staining test. The suspected colonies were then subjected to a primary test consisting of catalase and oxidase tests as well as biochemical tests with MRPV, TSIA, SIM, coagulase test and sugar test. The results showed that 23 samples (thirteen from pre-weaned pigs and ten from post-weaning pigs) were tested positive for Streptococcus sp. hemolytic ? (20 isolates) and Streptococcus sp. hemolytic ? (3 isolates).